The effect of financial ratio on financial distress during the Covid-19 pandemic : Case study of transportation sub sector companies listed on the Indonesia stock exchange period 2019–2020 - Wulanda Fitri; Robinhot Gultom; Ella Silvana Ginting (Institute of Accounting Research and Novation (IARN), 2022)
The purpose of this reserch is to determine and analyze the effect of the Current Ratio, Debt to Asset Ratio, Sales Growth and Total Asset Turnover simultaneously and partially on Financial Distress in the transportation sub-sector companies listed on the Indonesia Stock Exchange for the period of 2019-2020. The population of this study is the transportation sub-sector companies as many as 46 companies. The sampling method used purposive sampling, and the number of samples obtained are 33 companies. The type of the research is descriptive quantitative using logistic regression analysis method. The results show that the variables Current Ratio, Debt to Asset Ratio, Sales Growth, and Total Asset Turnover simultaneously affect Financial Distress in transportation sub-sector companies listed on the Indonesia Stock Exchange for the period of 2019-2020. Partially, Sales Growth have an effect, Current Ratio, Debt to Asset Ratio and Total Asset Turnover have no effect on Financial Distress in transportation sub-sector companies listed on the Indonesia Stock Exchange for period of 2019-2020.